I want to burn this place down : essays - Kreizman, Maris (Ecco, an imprint of HarperCollins Publishers, 2025)
"At the heart of this funny, acerbic, and bravely honest book of essays is Maris Kreizman, a former rule follower and ambition monster who once believed the following truths to be self-evident: that working very hard would lead to admission to a good college, which would lead to a good job at a good company, which would then lead to personal fulfillment and a sense of purpose, along with adequate health care and eventual home ownership and plenty of money waiting in a retirement account. Like any good Democrat and feminist, she believed that if she just worked hard and played by the rules, she was guaranteed a safe and comfortable life. Now in her forties, the only thing Maris Kreizman knows for sure is that she no longer has faith in American institutions or any of their hollow promises. Now she knows that the rules are meant to serve some folks better than others; and, actually, they serve no one all that well -- not even Kreizman. Disturbed by the depth and scope of the liberal myths in which she once so fervently believed, Kreizman takes readers on an intimate journey that revisits some of her most profound revelations, demonstrating that it's never too late to become radicalized. With Kreizman's signature wit and blunt self-reflection, and more than a little transformative rage, I Want to Burn This Place Down is a book for anyone who wishes they could go back in time to give their younger selves the real truth about the fractured country they have inherited -- and the encouragement to rebuild something better in its place." --